August Wilson's Fences: The African-American Women's Pursuit Of Dreams Seen From The Perspectives Of Rose Maxson - Kurnia, Nandy lntan (English Education Department, Universitas Islam Indonesia, 2010)
This paper portrays the struggle of people of color to reach their dreams as reflected in August Wilson's